Developing and Validating a Big-Store Multiple Errands Test - Antoniak, Kristen; Clores, Julie; Jensen, Danielle; Nalder, Emily; Rotenberg, Shlomit; Dawson, Deirdre R. (Frontiers in Psychology, 2019)
The Multiple Errands Test (MET) is an ecologically valid assessment that characterizes how executive dysfunction manifests in everyday activities. Due to the naturalistic nature of this assessment, clinicians and researchers have had to develop site-specific versions resulting in numerous published versions and making it difficult to establish standard psychometric properties. The aim of this study was to develop a standardized, community version of the MET designed to be used in large department stores meeting set criteria that would not require site specific modifications. This paper reports on the development, content validity, feasibility, and inter-rater reliability of a Big-Store MET, and the performance of healthy participants on this test. Items were selected to match previously published versions in relation to quantity and complexity. Content validity was established by having experts (n=4) on the MET review the proposed Big-Store version and evaluate the task consistency with previously published versions. To assess feasibility of administration, and inter-rater reliability, a convenience sample of 14 community dwelling adults, self-reporting as healthy, were assessed by two trained raters. We found the Big-Store MET to be feasible to deliver (completed within 30 minutes, scores show variability, acceptable to participants in community environment) and inter-rater reliability to be very high (ICCs =0.92-0.99) with the exception of frequency of strategy use. This study introduces the Big-Store MET to the literature, establishes its preliminary validity and reliability thus laying the foundation for a standardized, community-based version of the MET.